2019
DOI: 10.1108/jmtm-08-2018-0269
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of Industry 4.0: a descriptive survey in the Italian manufacturing sector

Abstract: Purpose The purpose of this paper is to investigate how much the Italian manufacturing companies are ready to be concretely involved in the so-called “Industry 4.0” (I4.0) journey. In particular, this paper focuses on analyzing the knowledge and adoption levels of specific I4.0 enabling technologies, also considering how organizations are involved and which are the main benefits and obstacles. Design/methodology/approach A descriptive survey has been carried out on a total of 103 respondents related to manuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 112 publications
3
74
0
14
Order By: Relevance
“…Finally, the authors present the results of applying their model on a heterogeneous sample of 20 SMEs in Bergamo, a city in the Northern part of Italy. These results provide a stepping stone toward the descriptive survey that reports results regarding Industry 4.0 for a larger sample of companies (see below Zheng et al, 2020).…”
Section: The Maturity and Readiness Cluster Assessing The Implementation Statusmentioning
confidence: 75%
See 2 more Smart Citations
“…Finally, the authors present the results of applying their model on a heterogeneous sample of 20 SMEs in Bergamo, a city in the Northern part of Italy. These results provide a stepping stone toward the descriptive survey that reports results regarding Industry 4.0 for a larger sample of companies (see below Zheng et al, 2020).…”
Section: The Maturity and Readiness Cluster Assessing The Implementation Statusmentioning
confidence: 75%
“…The tenth article with the title "The impacts of Industry 4.0: A descriptive survey in the Italian manufacturing sector", analyzes the knowledge and adoption levels of specific Industry 4.0 technologies (Zheng et al, 2020). The article sees levels of knowledge in a company regarding specific technologies as a good predictor of later adoption of the same technologies.…”
Section: The Survey and Model Cluster Measuring Implementation In Larger Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The problems of the development of Industry 4.0 are widely reflected in the works of many researchers: security and privacy in industry 4.0 (Alcaraz et al, 2020); safety digitalization (Savon et al, 2019); machine diagnostic methods applicability in the perspective of industry 4.0 (Asad et al, 2018); business intelligence (Bordeleau et al, 2019); national and regional comparative advantages in key enabling technologies (Ciffolilli & Muscio, 2018); model compression for IoT applications (Fu et al, 2020); prospects of using virtual technologies in modern corporate business systems (Klochko & Brizhak, 2019); modeling the management system of open innovation in E-economy (Kudryavtseva et al, 2018); Big Data approach (Kumar et al, 2018); digital supply chain model (Lizette Garay-Rondero et al, 2019); digitization and industry 4.0 optimization potential (Wirth & Klein, 2018); deep learning model in industry 4.0 (Ma et al, 2020); data science challenges (Piccialli et al, 2020); modelling of energy (Shinkevich et al, 2020); smart job shop under industry 4.0 (Wang et al, 2020); the impacts of industry 4.0 (Zheng et al, 2019) and ext.…”
Section: Problem Statementmentioning
confidence: 99%
“…That particular study also mentions that the main impact can be seen in increasing manufacturing process efficiency, which can be related to the highest importance being given to hardware and software connectivity and flexibility, which increases process efficiency [49]. In Italian companies, the highest importance was given to cloud computing technologies, ICT integration (machinery, electronic equipment and database), but also the use of new technologies (i.e., additive manufacturing), has shown to be one of the priorities for digital transformation strategy [50], while another research (also from Italy) has shown that many of the participants from the industry have no knowledge of cloud-based technologies and the use of augmented and virtual reality in the working environment, which is similar to Croatian companies [51]. Research conducted in Polish companies also implied high importance of investment in new hardware and software technologies, but also in human resources [52], while research from South Africa has shown a similar result of importance in innovativeness level, but also the difference in big data system development, where their result has shown very high awareness of the benefits from this kind of data processing, unlike Croatian companies, who are still mostly not aware of importance of this key Industry 4.0 element [53].…”
Section: Lean Tools 12%mentioning
confidence: 99%